Postneoadjuvant surveillance and surgery as needed compared with postneoadjuvant surgery on principle in multimodal treatment for oesophageal cancer: a scoping review protocol. Issue 1 (28th January 2021) - Schmucker, Christine; Nagavci, Blin; Hipp, Julian; Schmoor, Claudia; Meerpohl, Joerg; Hoeppner, Jens
Abstract : Introduction: In current medical practice of curative treatment for non-metastatic oesophageal cancer, surgery on principle is carried out by oesophagectomy after neoadjuvant treatment. However, oesophagectomy is often associated with postoperative morbidity and mortality. Taking into account that modern neoadjuvant therapy is effective and many of patients show no vital tumour cells in the operative specimens, we aim to perform a scoping review as part of the development phase for a prospectively planned multicentre randomised controlled trial investigating 'surgery as needed vs surgery on principle in patients with postneoadjuvant complete response of oesophageal cancer' (Prospective trial registration number DRKS00022801). This scoping approach will allow us to finally define and/or adapt the research question including the design and methodology of the randomised controlled trial taking into account the findings for example, research gaps and/or pitfalls in the currently available study pool addressing this or very similar questions. Methods and analysis: To identify relevant research, we will conduct searches in the electronic databases Medline, Web of Science Core Collection, Cochrane Library and Science Direct. We will also check references of relevant studies and perform a cited reference research (forward citation tracking). Titles and abstracts of the records identified by the searches will be screened and full texts of all potentially relevant articles will be obtained. We will consider randomised trials and non-randomised controlled studies. Data extraction tables will be set up, including study and patients' characteristics, aim of study and reported outcomes. We will summarise the data using tables and figures (eg, bubble plots) to present the research landscape and to describe potential clusters and/or gaps to support the planning of a randomised trial in this patient population. Ethics and dissemination: Ethical approval is not required for this scoping review. Study findings will be shared by publication in a peer-reviewed journal and by presentation to key stakeholders on scientific meetings.